Knowledge sharing intention, attitudes and workplace emotions at a bank in Malaysia - Hassan, Irwan Shahrani; Abdul Hamid, Zabeda; Omar, Azura (Academic Conferences Limited, 2019)
The rapid growth of the financial industry is putting a demand on banks to look for better ways to manage its corporate strategies. One of the ways to achieve that aim is through knowledge management. This research investigated knowledge sharing (KS) intention and behaviour as part of the corporate strategies in a prominent Malaysian government-linked financial institution, Bank Co. Both quantitative and qualitative approaches were utilised during the data collection process, which consisted of questionnaire survey, focus group discussions, and a review of the organisation's documents on knowledge management. In-depth perceptions among Bank Co.'s staff were explored that covered key areas; including knowledge sharing intention, workplace emotions, and attitudes. The quantitative data was analysed using descriptive statistical analysis while the qualitative data was analysed using content analysis. Two main theories were used as the framework for this research. The main theory, Knowledge Creation Theory (KCT), highlighted the main concern of this current research, which is the knowledge creation processes in the organisation which includes the employees' KS intention. Meanwhile, the Affective Event Theory (AET) was used to identify the themes related to workplace emotions, which influenced the attitudes towards KS intention at the workplace. The conclusions based on the findings of this research indicated that the staff's perceived KS behaviours in Bank Co. were influenced by their emotions and attitudes. In terms of methodology, this research added new perspectives to theories related to KS at the workplace as well as provided a foundation for discussing government agencies' treatment of KS. This discussion may encourage reforms of the existing knowledge management structures and practices. In addition, this research could serve as a basis for future research in this area, not just within the government-linked banks but other industries as well. From the practical perspective, this research provided Bank Co. with the opportunity to better understand to what extent their KS initiatives have succeeded. This can assist Bank Co. in designing programmes that can encourage productive KS behaviours within the organisation